Identifying the Potential of Work‐Sharing as a Job‐Creation Strategy - Skuterud, Mikal (Journal of Labor Economics, 2007)
Between 1997 and 2000, the Canadian province of Quebec reduced its standard workweek from 44 to 40 hours with the aim of stimulating employment growth. Unlike the European work‐sharing policies examined elsewhere, the Quebec policy contained no suggestion or requirement that employers provide wage increases to compensate workers for lost hours. For this reason, among others, the Quebec policy provides a better test of the potential of work‐sharing as a job‐creation strategy. The evidence suggests that, despite a 20% reduction among full‐time workers in weekly hours worked beyond 40, the policy failed to raise employment at either the provincial level or within industries where hours of work were affected relatively more.